Transformative Praxis at Work in Loreto Day School Sealdah: A Remarkable Fostering of Positive Peace - Hrynkow, Christopher; Creamer, David (In Factis Pax: Journal of Peace Education and Social Justice, 2015)
This article employs Edmund O’Sullivan transformative learning theory to map the remarkable educational programming at Loreto Day School Sealdah in Kolkata, India. Drawing on the authors’ personal experience of the school over several years, supplemented by a two day in-depth interview conducted near Manchester, England (October, 2013),2 it will illustrate how Loreto Day School’s praxis-based work sets significant challenges for educational practice intent on fostering the realization of substantive peace in this world. More specifically, this article will highlight pedagogical insights discerned by O’Sullivan and some of his interlocutors, which can help nurture positive peace through discussions organized around the transformative learning areas of (1) personal and social transformation, (2) contextual education, (3) education for social justice, and (4) participatory education. It will end by situating Loreto Day School Sealdah as a location of active hope.